2016
DOI: 10.5604/17322693.1207511
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of regulatory T cells and selected cytokines in the pathogenesis of bronchial asthma

Abstract: Asthma pathogenesis is complex and involves the interplay of many factors and actions. Airway inflammation in allergic asthma is characterized by an exaggerated activation of T helper type 2 cells, IgE production and infiltration and activation of eosinophils. The results of studies conducted in recent years indicate that the deficit of naturally occurring Foxp3+CD25+CD4+ and Foxp3+CD25+CD8+ regulatory T cells and type 1 regulatory T cells plays a pivotal role in the development of this disease. Moreover, nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Probably, it also serves as a growth factor receptor and regulates the proliferation of lymphocyte B. 35,36 Aside from CLL, a high expression of this molecule was also detected on the surface of B cells in promyelocytic and hair-cell leukemia. 37,38 The expression of CD25 on the surface of lymphocytes and an elevated serum concentration of soluble CD25 are associated with a negative prognosis in acute lymphoblastic leukemia and diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, it also serves as a growth factor receptor and regulates the proliferation of lymphocyte B. 35,36 Aside from CLL, a high expression of this molecule was also detected on the surface of B cells in promyelocytic and hair-cell leukemia. 37,38 The expression of CD25 on the surface of lymphocytes and an elevated serum concentration of soluble CD25 are associated with a negative prognosis in acute lymphoblastic leukemia and diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…While significant increases in Il-4 were observed at both time points, the fold-increase was greater for the longer exposure duration supporting a more pronounced T H 2 response. Increases in Il-10 , another T H 2 cytokine that has been shown to have a role in allergic disease (Zuska-Prot et al 2016), were also observed following the extended DDAB application at high concentration. In addition, secretion of IL-10 mediates the function of T reg cells (Sojka et al 2008; Corthay 2009; Kimber et al 2012) which have demonstrated a critical role in the development of immune tolerance by serving as effectors helping to prevent overzealous allergic responses (Sojka et al 2008; Yadav et al 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Asthma pathogenesis with involvement of many cytokines remains unsolved public health concern [1][2][3]13]. Despite the evident correlation between BA symptoms and ARVI especially with the hRV or the RSV both in the adult patients and in the children (Table 1) a certain conclusion about a role of the respiratory viruses in BA development, exaсerbations or as a consequence of binding of the hRV with the ICAM-1 receptor with enhanced level of the corresponding gene expression is hardly possible.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a multifactorial disease characterized by chronic airway inflammation, bronchial hyperresponsiveness, smooth muscle contraction, hypertrophy and hyperplasia of smooth muscle, hypersecretion of bronchial mucus, activation of mast cells, eosinophils, lymphocytes, epithelial cells, macrophages, disruption of the bronchial epithelium, and production of free radicals such as expired nitric oxide (eNO) and 8-isoprostane [1][2][3]. Currently, the disease is widely spread among 4-10% of the world population; in Russia in approximately 7 million [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation